The Modied Simple Equation Method and its Applications in Mathematical Physics and Biology (Global Journal of Science Frontier Research, 2015)
In this paper, the modified simple equation method with the aid of Maple is used to obtain new exact traveling wave solutions of the system of shallow water wave equations, modified Benjamin-Bona-Mahony equation and nonlinear dynamics of microtubules-A new model. When these parameters are taken special values, the solitary wave solutions are derived from the exact traveling wave solutions. It is shown that the modified simple equation method provides an effective and a more powerful mathematical tool for solving nonlinear evolution equations in mathematical physics. Comparison between our results and the wellknown results will be presented.
Keywords: the system of shallow water wave equations; modified benjamin-bona-mahony equation; nonlinear dynamics of microtubules; the modified simple equation m